Synthesis, crystal structure and characterization of a lanthanide complex based on 4-(4-oxypyridinium-1-yl) phthalic acid and 1,10-phenanthroline - Zhang, T.; Li, R.F.; Feng, X.; Ng, S.W.; Bai, RF. (Taylor & Francis, 2017)
A new lanthanide complex [(Ho(L)(phen)NO3(H2O)] H2O (1) (H2L D 4-(4-Oxypyridinium -1-yl) phthalic acid, phen D 1,10-phenanthroline) has been afforded under hydrothermal conditions, and characterized by elemental analysis, IR spectra, and X-ray diffraction. In the structure of 1, the L ligand connects Ho(III) atoms through one monodentate and one chelate carboxylate as well as one hydroxy group giving rise to a 2D wavelike polymer layer, which is extended by C–H O hydrogen bond and π π stacking interactions to give rise to a 3D supramolecular network. In addition, PXRD patterns and thermal gravimetric analysis (TGA) of sample 1 were investigated.